Experimental simulation of crude oil-water partitioning behavior of BTEX compounds during a deep submarine oil spill. (June 2017) - Jaggi, Aprami; Snowdon, Ryan W.; Stopford, Andrew; Radović, Jagoš R.; Oldenburg, Thomas B.P.; Larter, Stephen R.
Graphical abstract: Highlights: BTEX partitioning in deepwater oil spill was simulated using custom-made equipment. Partitioning trends were measured at water column PT conditions from 200–1500 m depth. From sea floor to shallow depths, BTEX partition ratios decrease by ∼3 times. Methane concentration in oil significantly affects the extent of BTEX partitioning. Gas charge (live oil) has a larger impact vs temperature on partitioning behavior. Abstract: The conventional shake flask technique for determining oil-water partition ratios of benzene, toluene, ethylbenzene and xylene (BTEX) cannot accurately assess the extremes of high pressure and low water temperatures found in submarine oil spill conditions. An oil-water partitioning device has been constructed to experimentally simulate the partition behavior of BTEX compounds under submarine oil spill conditions, using simulated live oil (methane-charged), with saline waters over a range of pressure (2–15 MPa) and temperature (4–20 °C). Within the investigated ranges, the partition ratios of BTEX compounds increase proportionally with an increase in methane charging pressure (oil saturation pressure) and the degree of BTEX alkylation, and decrease with increase in temperature. The variation of the partition ratio values due to changes in system pressure and increasing oil methane concentration, is much more significant than those seen due to change in the temperature over the range studied. This data may be used in near-field and far-field distribution modeling of the environmental fate of highly toxic BTEX compounds, derived from submarine oil spills and their impact on the ecosystem. The parameters will also aid in the prediction of oil migration and dispersion away from the spill thus helping to improve response strategies.